Identificação de pragas na agricultura utilizando APIs de visão computacional - Vilas Boas, Lenilson Lemos (2018)
Systems that use Computer Vision Application Program Interfaces (APIs) can learn and identify patterns and thus perform associations to retrieve additional data. They are able to obtain results much faster than any human agent is. The study uses three computational vision APIs and evaluates their application in the identification of four plant leave diseases. Based on a corpus of fifty images, the API training was conducted in two stages, the first with thirty images and the second training with twenty more images. After the two trainings, the results of the diseases were collected for each API studied, which made it possible to evaluate the identification capacity and its evolution of learning after each training. The results corroborated the hypothesis. They gave evidence of the feasibility of identification of plant leaf diseases by means of computer vision APIs